Roxadustat attenuates hyperoxia-induced lung injury by upregulating proangiogenic factors in newborn mice - Liang-Ti Huang; Hsiu-Chu Chou; Chung-Ming Chen (Pediatrics and Neonatology)
Background: Premature infants who require oxygen therapy for respiratory distress syndrome often develop bronchopulmonary dysplasia, a chronic lung disease characterized by interrupted alveologenesis. Disrupted angiogenesis inhibits alveologenesis; however, the mechanisms through which disrupted angiogenesis affects lung development are poorly understood. Hypoxia-inducible factors (HIFs) are transcription factors that activate multiple oxygen-sensitive genes, including those encoding for vascular endothelial growth factor (VEGF). However, the HIF modulation of angiogenesis in hyperoxia-induced lung injury is not fully understood. Therefore, we explored the effects of roxadustat, an HIF stabilizer that has been shown to promote angiogenesis, in regulating pulmonary angiogenesis on hyperoxia exposure. Methods: C57BL6 mice pups reared in room air and 85% O2 were injected with phosphate-buffered saline or 5 mg/kg or 10 mg/kg roxadustat. Their daily body weight and survival rate were recorded. Their lungs were excised for histology and angiogenic factor expression analyses on postnatal Day 7. Results: Exposure to neonatal hyperoxia reduced body weight; survival rate; and expressions of von Willebrand factor, HIF-1α, phosphor mammalian target of rapamycin, VEGF, and endothelial nitric oxide synthase and increased the mean linear intercept values in the pups. Roxadustat administration reversed these effects. Conclusion: Hyperoxia suppressed pulmonary vascular development and the expression of proangiogenic factors. Roxadustat promoted pulmonary angiogenesis on hyperoxia exposure by stabilizing HIF-1α and upregulating the expression of proangiogenic factors, indicating its potential in clinical and therapeutic applications.